Lifestyle modifications among older adults with prehypertension in primary care - Boonsaad, Potsunee; Chompoopan, Worawut (Intelektual Pustaka Media Utama, 2024)
In both global and Thai contexts, unhealthy behaviors such as alcohol consumption, smoking, excessive salt intake, and sedentary lifestyles contribute to hypertension. World Health Organization (WHO) recommends lifestyle adjustments for blood pressure control. This quasi-experimental study examined the impact of an intervention on elderly individuals with prehypertension. People living in two villages were selected, matching two others demographically and geographically. The intervention focused on a balanced diet, physical activity, stress management, and reduced tobacco/alcohol use with a low-sodium diet. Blood pressure and heart rate were measured three times after a 10-minute rest using a calibrated sphygmomanometer. The study showed significant improvements with p<0.001. Systolic blood pressure decreased by 5.94 mmHg, diastolic blood pressure decreased by 3.37 mmHg, and heart rate decreased by 4.12 bpm. The findings emphasize the importance of comprehensive lifestyle modifications to manage prehypertension and reduce hypertension-related complications in older people. Further research and interventions are needed to address people with hypertension globally, including in Thailand.